ANALYSIS OF CASH, CERTIFICATE OF BANK INDONESIA, ALLOWANCE FOR UNCOLLECTIBLE ACCOUNTS AND ASSETS IN FOREIGN CURRENCIES ON THE PROFITABILITY AT PT. BPR DANA RAYA - Massie, Yuanita Stella (Universitas Sam Ratulangi, 2015)
Profit is the main thing that always been desired by the Rural Bank. In an organization, must have a maximum achievement that the goal can be fulfilled. The purpose of this study is to determine how much influence of cash, certificate of BI, allowance for uncollectible accounts, and assets in foreign currencies on the profitability at PT. BPR Dana Raya. This research is a quantitative approach and using a multiple regression method. This type of research and method can measure the amount of advantage gained each year in PT. BPR Dana Raya. At first the bank is only a small private bank that just started operating in 2010 in Manado. But after four years of running this bank already has several branches in several areas of North Sulawesi. As 4 years is a short time and is not easy to develop a business such as rural banks. The source to know the advantages of this bank, which is from annual financial reports for 4 years from 2010 to 2014. In managerial role should consider about the Profitability since it is the most crucial part of the company and how the company should go public, so that the people will invest their money to the company. Keywords: cash, certificate, uncollectible accounts, assets, profitability.